1997
DOI: 10.1172/jci119789
|View full text |Cite
|
Sign up to set email alerts
|

Allergen-induced increases in IL-5 receptor alpha-subunit expression on bone marrow-derived CD34+ cells from asthmatic subjects. A novel marker of progenitor cell commitment towards eosinophilic differentiation.

Abstract: We have proposed previously that hemopoietic myeloid progenitors contribute to the ongoing recruitment of proinflammatory cells, namely eosinophils, to sites of allergen challenge in allergic diseases such as asthma. In this study, we investigated the involvement of bone marrow-derived progenitors in the development of allergen-induced pulmonary inflammation in mild asthmatic subjects. By flow cytometry, we enumerated the level of expression of CD34, a hemopoietic progenitor cell marker, on bone marrow aspirat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
196
0
4

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 224 publications
(212 citation statements)
references
References 44 publications
12
196
0
4
Order By: Relevance
“…This high frequency of IL-5R staining in mice is in contrast to that in humans, in which much smaller numbers of bone marrow cells express this epitope. Furthermore, in humans this receptor also seems to be up-regulated by allergen exposure in asthmatics developing a late asthmatic reaction (15). This is in parallel with increased number of CFUs producing eosinophils in bone marrow samples taken after allergen exposure (24).…”
Section: Discussionmentioning
confidence: 96%
“…This high frequency of IL-5R staining in mice is in contrast to that in humans, in which much smaller numbers of bone marrow cells express this epitope. Furthermore, in humans this receptor also seems to be up-regulated by allergen exposure in asthmatics developing a late asthmatic reaction (15). This is in parallel with increased number of CFUs producing eosinophils in bone marrow samples taken after allergen exposure (24).…”
Section: Discussionmentioning
confidence: 96%
“…Presence of this additional eosinophil-differentiation pathway is supported by reports showing that allergic subjects have increased numbers of the eosinophil-lineage-committed CD34 ϩ cells in BM 12 and AW 13 and that AW CD34 ϩ cells can complete their differentiation following ex vivo stimulation with interleukin 5 (IL-5) or allergen. 14 However, whether these cells retain their ability to multiply within AW and subsequently maturate into eosinophils in vivo is not known.…”
Section: Introductionmentioning
confidence: 84%
“…Recent studies have shown that eosinophil precursors in BM are identifiable as CD34 + /IL-5R § + cells [35]. CD34 is an O-sialylated glycoprotein, whose expression within the hemopoietic system is restricted to primitive progenitor cells of all lineages [36], while IL-5R expression is essentially limited to eosinophil and basophil lineages [37,38]. We found that most of the IL-5R § + cells in BM were CD34 + cells in our model (data not shown).…”
Section: Discussionmentioning
confidence: 99%